FOXI1 immunohistochemistry differentiates benign renal oncocytoma from malignant chromophobe renal cell carcinoma - Molnár, Ágnes; Kovacs, Gyula (Anticancer research, 2019)
Background/Aim: Renal oncocytoma (RO) and chromophobe renal cell carcinoma (chRCC) are suggested to develop from α- and β-intercalated (IC) cells of the collecting duct expressing solute carrier family 4 member 1 (SLC4A1) and SLC26A4 under control of forkhead box 1 (FOXI1) transcription factor. The aim of this study was to clarify the possible cellular origin and of RO and chRCC. Materials and Methods: Immunohistochemistry for aquaporin 2 (AQP2), FOXI1, SLC4A1 and SLC16A4 was applied to distinct types of renal cell tumors. Results: Nuclear FOXI1 staining occurred in 96% of 83 ROs, in 3% of 90 chRCCs and none of the other tumor types. The α-IC cell marker SLC4A1 was seen in 60% of RO and 11% of chRCC, whereas staining for the β-IC cell marker SLC26A4 was negative in all but one tumor. Conclusion: Although the origin of RO remains unclear, our findings suggest that FOXI1 immunohistochemistry is useful in differential diagnosis of RO from chRCC with overlapping histology.